Statistical methods for trend detection and analysis in the environmental sciences - Chandler, R. E. (Richard E.); Scott, E. Marian (Chichester, West Sussex, U.K. : Wiley, 2011)
'Statistical methodology itself has made some significant developments in areas that are highly relevant to the problems faced by environmentalists; thus this book fills a gap in the market in which there is currently a lot of interest. Split into two parts, part 1 - Theory and methods - introduces the basis for and scope of the book, and covers amongst others the chief topics of exploratory analysis, non-parametric estimation and testing, and parametric modeling. Part 2 - Case Studies - introduces a number of co-authors, specialists in their own areas of environmental science, to illustrate the application of the theory and methods in practice. The accompanying website develops the practical aspects raised in the book, and provides a useful complementary tool.'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Environmental sciences -- Statistical methods